The Connection Between Health Education, Exclusive Breastfeeding, and Infant Weight Gain : A Scoping Review - Shilvia Shilvia; Zulvayanti Zulvayanti; Dewi Marhaeni Diah Herawati; Hadi Susiarno; Dany Hilmanto; Setyorini Irianti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
This study aims to explore the relationship between health education, exclusive breastfeeding, and infant weight gain. Exclusive breastfeeding is recognized as the best nutrition for infants; however, adherence to breastfeeding practices is often influenced by the mother's level of education. Through a scoping review approach, we collected and analyzed a total of 10 recent studies that discuss the impact of health education on mothers' attitudes and behaviors regarding exclusive breastfeeding, in line with the PRISMA framework. The analysis results indicate that mothers with adequate health education are more likely to understand the benefits of exclusive breastfeeding and demonstrate a stronger commitment to it. Additionally, optimal exclusive breastfeeding contributes to healthy growth and weight development in infants. These findings emphasize the importance of health education interventions in supporting successful breastfeeding practices, which can improve infants' nutritional status. Further research is needed to explore additional factors influencing this relationship and to formulate more effective strategies for promoting exclusive breastfeeding. Keyword: Health Education, Exclusive Breastfeeding, Infant Weight Gain